Lemmings : le récit de science-fiction et le « vice de forme » - Jean Nimis (ReS Futurae)
The article compares two short stories by two writers who are very different and relatively distant from one another in space and time. For both, the same animal metaphor (the legendary suicidal race of lemmings) expresses an essential concern : the human becoming of mankind and his possible extinction. In each case, thanks to its poetic characteristics, the brief form allows the effective transmission of an ethical message (the « inherent defect » suggested by Primo Levi) and it gives an account of a « time binding » (Robert Heinlein).